Decreased Inflammatory Responses of Human Lung Epithelial Cells after Ethanol Exposure Are Mimicked by Ethyl Pyruvate - Relja, B.; Omid, N.; Kontradowitz, K.; Jurida, K.; Oppermann, E.; Störmann, P.; Werner, I.; Juengel, E.; Seebach, C.; Marzi, I. (Mediators of Inflammation, 2014)
Background and Purpose. Leukocyte migration into alveolar space plays a critical role in pulmonary inflammation resulting in lung injury. Acute ethanol (EtOH) exposure exerts anti-inflammatory effects. The clinical use of EtOH is critical due to its side effects. Here, we compared effects of EtOH and ethyl pyruvate (EtP) on neutrophil adhesion and activation of cultured alveolar epithelial cells (A549). Experimental Approach. Time course and dose-dependent release of interleukin- (IL-) 6 and IL-8 from A549 were measured after pretreatment of A549 with EtP (2.5–10 mM), sodium pyruvate (NaP, 10 mM), or EtOH (85–170 mM), and subsequent lipopolysaccharide or IL-1beta stimulation. Neutrophil adhesion to pretreated and stimulated A549 monolayers and CD54 surface expression were determined. Key Results. Treating A549 with EtOH or EtP reduced substantially the cytokine-induced release of IL-8 and IL-6. EtOH and EtP (but not NaP) reduced the adhesion of neutrophils to monolayers in a dose- and time-dependent fashion. CD54 expression on A549 decreased after EtOH or EtP treatment before IL-1beta stimulation. Conclusions and Implications. EtP reduces secretory and adhesive potential of lung epithelial cells under inflammatory conditions. These findings suggest EtP as a potential treatment alternative that mimics the anti-inflammatory effects of EtOH in early inflammatory response in lungs.